Theology of the New Testament ; v.2 - Bultmann, Rudolph Karl, 1884-1976; Grobel, Kendrick (London, UK SCM, 1955)
Contents : v. 2 : The theology of John; The development of church order and doctrine; The problem of Christian living. Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- theology